2011
DOI: 10.1038/nature10694
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cancer stem cells and their niche govern metastatic colonization

Abstract: Metastatic growth in distant organs is the major cause of cancer mortality. The development of metastasis is a multistage process with several rate-limiting steps 1 . Although dissemination of tumour cells seems to be an early and frequent event 2 , the successful initiation of metastatic growth, a process termed 'metastatic colonization', is inefficient for many cancer types and is accomplished only by a minority of cancer cells that reach distant sites 3,4 . Prevalent target sites are characteristic of many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

46
996
1
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,160 publications
(1,075 citation statements)
references
References 34 publications
46
996
1
11
Order By: Relevance
“…Several recent studies implicated fibroblasts in facilitating formation of the metastatic niche: O'Connell et al reported that resident FSP-1 + fibroblasts express VEGF-A and tenascin-C that correlated with increased metastasis in a mouse model of transplantable mammary carcinoma -depletion of fibroblasts or genetic ablation of VEGF-A and tenascin-C resulted in decreased metastatic capacity [102]. These results are supported by the findings of two other groups, demonstrating that expression of the ECM proteins tenascin-C and periostin by stromal fibroblasts in the lungs supports the formation of a metastatic niche that facilitates metastatic colonization of mammary tumour cells, by enhancing WNT signalling [103][104][105]. Expression of periostin by pancreatic stellate cells was also suggested to be in correlation with aggressive behaviour and worse prognosis in pancreatic cancer [106].…”
Section: Cafs Modulate the Metastatic Nichementioning
confidence: 54%
“…Several recent studies implicated fibroblasts in facilitating formation of the metastatic niche: O'Connell et al reported that resident FSP-1 + fibroblasts express VEGF-A and tenascin-C that correlated with increased metastasis in a mouse model of transplantable mammary carcinoma -depletion of fibroblasts or genetic ablation of VEGF-A and tenascin-C resulted in decreased metastatic capacity [102]. These results are supported by the findings of two other groups, demonstrating that expression of the ECM proteins tenascin-C and periostin by stromal fibroblasts in the lungs supports the formation of a metastatic niche that facilitates metastatic colonization of mammary tumour cells, by enhancing WNT signalling [103][104][105]. Expression of periostin by pancreatic stellate cells was also suggested to be in correlation with aggressive behaviour and worse prognosis in pancreatic cancer [106].…”
Section: Cafs Modulate the Metastatic Nichementioning
confidence: 54%
“…The tumour stromal compartment has been shown to have an important role in metastasis [14][15][16] . Within the tumour stroma, bone marrow-derived cells, specifically myeloid, have been identified as regulators of tumour invasiveness and implicated in organ-specific tumour metastasis 17,18 .…”
mentioning
confidence: 99%
“…7,[43][44][45][46][47][48][49][50] NOTCH PATHWAY Mammalian cells express four transmembrane Notch receptors including NOTCH-1, NOTCH-2, NOTCH-3 and NOTCH-4. [43][44][45][46][47][48][49][50] Notch signaling has been implicated in selfrenewal in CSCs in a variety of cancers. Notch receptors are expressed during the development of thyrocytes in experimental systems and the expression levels of these receptors are aligned with thyroid differentiation markers.…”
mentioning
confidence: 99%